The runes of engagement - Buckell, Tobias S.; Klecha, Dave (Tachyon, 2024)
No one could have been prepared for the day when orcs, trolls, and dragons fell from portals in the sky. But now a very tough but not-quite-prepared platoon of Marines is trapped on the wrong side. The enchanting world looks like Middle Earth, but to the dismay of even the geekiest soldiers, is nothing like it. While the Marines fend off dangerous, improbable, and very rude assailants, their mission is to escort a Very Important Princess who could broker a crucial strategic alliance between worlds. What could possibly go wrong?